2001
DOI: 10.1097/00004850-200107000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol augmentation for poorly responsive schizophrenia

Abstract: Adenosine has been proposed to contribute to the pathophysiology of schizoprenia and as a target for therapeutic intervention. In the lack of direct adenosine agonists, allopurinol may indirectly elevate adenosine levels by inhibiting degradation of purines. We report two cases of poorly responsive schizophrenic patients who improved considerably with add-on allopurinol 300 mg/day. Their clear clinical improvement warrant further investigation of allopurinol, as well as other purinergic strategies, for the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 21 publications
0
26
0
1
Order By: Relevance
“…Conventional antipsychotic drugs were not designed to modulate the dopaminergic and glutamatergic systems concomitantly, which might be needed to achieve more efficient treatment of the positive, negative, and cognitive symptoms of schizophrenia; however, manipulating adenosine as an upstream regulator of both dopamine and glutamate might offer such a concomitant treatment approach. A link between adenosine hypofunction and schizophrenia is also supported by clinical evidence: increased enzymatic degradation of adenosine by adenosine deaminase has been detected in patients with schizophrenia (11,12), whereas allopurinol, a purine degradation inhibitor that increases adenosine tone, has shown clinical efficacy as add-on therapy for schizophrenia (13,14).…”
Section: Introductionmentioning
confidence: 95%
“…Conventional antipsychotic drugs were not designed to modulate the dopaminergic and glutamatergic systems concomitantly, which might be needed to achieve more efficient treatment of the positive, negative, and cognitive symptoms of schizophrenia; however, manipulating adenosine as an upstream regulator of both dopamine and glutamate might offer such a concomitant treatment approach. A link between adenosine hypofunction and schizophrenia is also supported by clinical evidence: increased enzymatic degradation of adenosine by adenosine deaminase has been detected in patients with schizophrenia (11,12), whereas allopurinol, a purine degradation inhibitor that increases adenosine tone, has shown clinical efficacy as add-on therapy for schizophrenia (13,14).…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, transgenic mice overexpressing adenosine kinase, a cytosolic ribokinase that phosphorylates the re-uptaken adenosine into 5′-adenosine monophosphate (AMP), show attention impairments linked to SZ, while adenosine augmentation exerts antipsychotic-like activity in mice [11]. In fact, several clinical trials have shown the beneficial effects of drugs that modulate adenosine signalling such as allopurinol and dipyridamole, which increase extracellular adenosine levels by inhibiting its degradation and reuptake, respectively [12][13][14][15][16][17]. Interestingly, caffeine (a non-selective adenosine receptor antagonist) consumption exacerbates psychotic symptoms in SZ patients [18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that adenosine is a regulator of the bioenergetics network that has been observed to modulate both glutamatergic and dopaminergic neurotransmission. 36 Moreover, Lara et al 37 suggested that dysfunction in purine metabolism would result in decreased levels of adenosinergic activity, which will cause an imbalance between glutamatergic and dopaminergic neurotransmission. This mechanism is accepted as the milestone of the pathophysiology of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…38 Allopurinol, an XO inhibitor, has already been studied as an additional treatment method in schizophrenia patients. 19,37,39 It functions as an inhibitor in the major degradation pathway of purines and is strongly believed to increase levels of purines, including adenosine. 18 In our experimental model, we determined that XO levels were significantly reduced (P = 0.0001) in the paliperidone group.…”
Section: Discussionmentioning
confidence: 99%